Clinical Evaluation of Patients with Spinal Cord Infarction in Mashhad, Iran - Kavian Ghandehari; Mohammad Reza Gerami Sarabi; Parham Maarufi (Stroke Research and Treatment)
Background. Spinal Cord Infarction (SCI) is a rare and disabling disease. This hospital-based study was conducted for clinical evaluation of SCI patients in east of Iran. Methods. Consecutive SCI patients admitted in Ghaem hospital,Mashhad during 2006–2010 were enrolled in a prospective clinical study. Diagnosis of SCI was made by neurologists and radiologists. Demographic features, clinical syndrome, and Magnetic Resonance Imaging (MRI) findings were recorded. All of the patients underwent a standard battery of diagnostic investigations. All of the patients suspected to SCI had MRI of spinal cord at the symptomatic level of cord with a 0.5 Tesla generation, Philips NT Intra, Netherland equipment. An equal number of patients with Brain Infarction (BI) were randomly selected from our stroke registry data bank. Etiology and degree of disability were compared between these groups of patients. Results. Fourteen SCI patients (9 females, 5 males) with mean age 38.8±SD: 19.9 years were evaluated. Miscellaneous causes consisted 50% of etiologies in patients with SCI. Uncertain etiology, atherosclerosis, and cardioembolisms consisted 35.7%, 7.1%, and 7.1% of SCI causes, respectively. Distribution of etiologies was significantly different between SCI and BI patients, X2=12.94, df=3, P=.003. Difference in mean disability score at acute phase of stroke was not significant between two studied groups, z=1.54, P=.057. Difference in mean changes of disability score at 90 days postevent was significant in two groups of patients, z=2.65, P=.019. Conclusion. SCI is a rare disease with poor recovery. Distribution of etiologies of SCI patients is quite different than of BI patients.